SOCIAL DETERMINANT OF COVID-19 RISKS AMONG CHILDREN IN JAKARTA, INDONESIA - Purwati, Nyimas Heny; Awaliah, Awaliah; Imroatun, Tri (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Pandemics have historically disproportionately impacted the poor and disadvantaged. Poverty, the external environment, and race or ethnicity can all significantly impact COVID-19 consequences. Those barriers, called social determinants of health (SDOH), are significant for many people's health. This study aimed to investigate the social determinants of COVID-19 risk among children in Jakarta, Indonesia. We recruited parents whose children were between 6 and 12 and were admitted to a general public hospital in Jakarta, Indonesia. Logistic regression was used to examine the relationship between socioeconomic status and COVID-19 risk. This analysis includes 200 parents of children aged 6 to 12 years old (60%) retrospectively recruited. About half of the parents had undertaken primary education level. No significant correlation was found between parent education level, occupation, and monthly income with COVID-19 risk among children. The number of house occupants more than two was positively associated with a higher risk of COVID-19 in children. In conclusion, poor housing conditions increase the probability of COVID-19 infection in Indonesian children. This implies that parental reinforcement of anti-household transmission strategies is necessary.